Behaviour based safety approach and factors affecting unsafe behaviour in construction sector: a review - Zerguine, Haroun; Jalaludin, Juliana; Mohd Tamrin, Shamsul Bahri (Environmental and Occupational Health Society, 2016)
Objective: Construction sector is a critical sector due to high accidents and fatality rates, while unsafe behaviours like hu- man errors and inappropriate operations has been reported as the main cause of accidents. The purpose of this review is to explore the factors influencing unsafe behaviour and to introduce the Behaviour Based Safety (BBS) approach for accident prevention triggered by those unsafe behaviours.